RISKS AND BENEFITS OF HORMONE THERAPY IN MENOPAUSE: A NARRATIVE REVIEW OF THE LITERATURE (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze the risks and benefits of hormone therapy in menopause. Bibliographic Review: The climacteric (or perimenopause) is defined by the World Health Organization as a physiological phase of life and not a pathological process, which comprises the transition between the reproductive and non-reproductive periods of a woman's life, a period in which menstrual irregularities and vasomotor complaints appear, preceding menopause. HRT emerged with the purpose of relieving symptoms and acting preventively, thus reducing the appearance of diseases, such as cardiovascular diseases and osteoporosis. The importance of HRT in improving climacteric symptoms, such as vasomotor symptoms and urogenital atrophy, is clear. However, less than 20% of postmenopausal women use this therapy. Final considerations: It should be noted that menopause is an important physiological event in female reproductive life, usually accompanied by important organic changes, which can affect women's quality of life. Knowledge of these changes becomes fundamental since women already spend a large part of their lives in this period. In addition, at the moment, hormone replacement therapy is the main alternative to minimize the symptoms of the climacteric.